PENERAPAN PERANGKAT PEMBELAJARAN BERBASIS PROBLEM BASED INSTRUCTION (PBI) UNTUK MELATIHKAN KARAKTER PEDULI LINGKUNGAN - SUBANDIYAH MEDP, LILIK (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2014)
The purpose of this describle to the result implemented of learning instrument based Problem Based Instruction (PBI) to practice of environmentally character. This type of research was a pre-experimental research. The method used was the one shot study with subjects 19 students class X MA Al-Khidmah Ngronggot Nganjuk. Parameters measured include: feasibility lesson plans, character, skill, mastery learning, and student responses. Instrument used to collect the data that management feasibility study sheets, the character of students, observation skills sheets, achievement test, and questionnaire responses. The technique is a method of collecting data observation, self-assessment, test method, and questionnaires. The result of implemented this learning instrument is lesson plan realized about 100%, environmentally character with average 7,16, assessment of student skill about 3,25, mastery of learning outcome classically about 84,21%, and student respond about 96,19%. Key word: Implementation of instrument learning, learning model (Problem Based Instruction), and environmentally character.